APPLICATION OF STRUCTURALLYSUPERFINE MODIFIERS FOR PROCESSING OF THE BLACK AND NONFERROUS METALS ALLOYS - V. Ju. Stetsenko (Литьë и металлургия)
It is shown that application of structural heredity allows to increase considerably the efficiency of the modifying process and modifiers activities. This allowed to develop universal structural-superfine silumin modifiers for modifying of black and nonferrous metals.